2020
DOI: 10.1152/ajprenal.00125.2020
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of low-dose sacubitril and/or valsartan on renal disease in salt-sensitive hypertension

Abstract: Diuretics and renin-angiotensin system blockers are often insufficient to control the blood pressure (BP) in salt-sensitive (SS) subjects. Abundant data support the proposal that the level of atrial natriuretic peptide may correlate with the pathogenesis of SS hypertension. We hypothesized here that increasing atrial natriuretic peptide levels with sacubitril, combined with renin-angiotensin system blockage by valsartan, can be beneficial for alleviation of renal damage in a model of SS hypertension, the Dahl … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 74 publications
0
11
0
Order By: Relevance
“…Figure 1 illustrates that the HS diet increases urinary volume and sodium excretion similarly to earlier reports. 34,35 HS diet and associated hypertension led to renal damage, which can be detected by elevated albuminuria. As shown in Figure 1B,C SS Nox4−/− rats demonstrated increased daily diuresis and natriuresis on day 3 of dietary intervention indicating improved pressure-natriuretic response at an early stage.…”
Section: Nox4 Deletion Increases Hs-induced Diuresis and Natriuresimentioning
confidence: 99%
“…Figure 1 illustrates that the HS diet increases urinary volume and sodium excretion similarly to earlier reports. 34,35 HS diet and associated hypertension led to renal damage, which can be detected by elevated albuminuria. As shown in Figure 1B,C SS Nox4−/− rats demonstrated increased daily diuresis and natriuresis on day 3 of dietary intervention indicating improved pressure-natriuretic response at an early stage.…”
Section: Nox4 Deletion Increases Hs-induced Diuresis and Natriuresimentioning
confidence: 99%
“…In our study, though BP was not significantly higher, we observed exacerbated renal hypertrophy in the SCB group, which commonly accompanies hypertension [ 60 , 61 ], and is caused in part by microvascular barotrauma [ 62 ]. In our previous study [ 43 ] with a lower dose of sacubitril, we reported no changes in kidney to body weight ratio in the SCB group. We can speculate that when sacubitril dosage is increased, in the absence of ARBs, sacubitril treatment results in increased RAS activation due to the side effects of neprilysin inhibition [ 33 ]; however, more extensive mechanistic studies are required to make definite conclusions.…”
Section: Discussionmentioning
confidence: 62%
“…Body weight was measured in both groups before the start of the HS challenge (on the NS diet) and after 21 days on the HS diet. Here, we chose to use the 125 μg/day dose of sacubitril (compared to 75 μg/day used by us previously [ 43 ], an average of ∼0.4 mg/kg/day was administered to rats throughout the protocol. For human patients, recommended starting oral dose of a combination drug (Entresto ® ) is 25–50 mg/twice a day (0.7–1.5 mg/kg/day for a 70 kg person).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations